Official Languages Recognition Program (OLRP) - Accreditation Canada (2022)
Accreditation Canada’s Official Languages Recognition Program (OLRP) supports and awards organizations that are committed to improving access to health and social services in official languages. This brochure answers questions such as: - How does the program work? - How does this program integrate with our current language accessibility efforts? - Who developed this program? - Why is this the right time to participate? - How much does it cost to participate in the program?

Programme de reconnaissance des langues officielles (PRLO) - Agrément Canada (2022)
Le Programme de reconnaissance des langues officielles (PRLO) d'Agrément Canada appuie et certifie les organismes qui sont engagés à améliorer l'accès aux services de santé et services sociaux en langues officielles. Ce feuillet d'information à l'intention des fournisseurs de services répond aux questions suivantes: - Comment le programme fonctionne‐t‐il ? - Comment ce programme s'intègre-t-il à nos efforts actuels d'accessibilité linguistique ? - Qui a élaboré ce programme ? - Pourquoi est-ce le bon moment de participer ? - Quel est le coût pour participer au programme ?

Compétences linguistiques et culturelles des organisations de santé. Analyse critique de la littérature - Aucoin, Léonard (InfoVeille Santé, 2008)

Inequality in fetal autopsy in Canada - Auger, Nathalie; Tiandrazana, Rémi- Claude; Healy-Profitós, Jessica; Costopoulos, André (Journal of health care for the poor and underserved, 2016)
Purpose. Inequality in use of fetal autopsy is poorly understood, despite the importance of autopsy in establishing the cause of stillbirth for future prevention. We examined fetal autopsy rates between linguistic minorities in Quebec, Canada, and assessed trends over three decades. Methods. Using registry data on 11,992 stillbirths from 1981–2011, we calculated fetal autopsy rates for Francophones, Anglophones, and Allophones by decade. Results. We found lower fetal autopsy rates for Allophones (54.4%) than Francophones (68.5%) and Anglophones (63.4%), but rates decreased over time for all language groups. After 2000, Allophones had 25% higher risk of non-autopsy relative to Francophones, with 8.8 fewer autopsies for every 100 stillbirths. Allophones who were not autopsied had 32% higher risk of having an undetermined cause of death. Conclusion. Inequality in use of fetal autopsy may be widespread for minorities in Canada. Efforts to decrease stillbirth in minorities may require policies to increase autopsy rates.

L’accès aux soins de santé pour les communautés minoritaires de langue officielle : fondements juridiques, initiatives actuelles et perspectives d’avenir - Bélanger, Mauril; Comité permanent des langues officielles (Gouvernement du Canada, Chambre des communes, 2003)

Programme d’accès aux services de santé et aux services sociaux en langue anglaise de la Côte-Nord - Bilodeau, Nancy; Paradis, Pascal; Morin, Sandra (Agence de la santé et des services sociaux de la Côte-Nord, 2011)

Les minorités linguistiques du Canada et la santé - Bouchard, Louise; Desmeules, Martin (Politiques de santé, 2013)
Résumé Les minorités de langue officielle (les francophones hors-Québec et les anglophones du Québec) représentent près de 6,4 % de la population canadienne. Bien que le français et l’anglais aient un statut d’égalité juridique selon la Constitution canadienne, il y a lieu de s’interroger sur leur égalité dans le domaine de la santé : les communautés francophones et anglophones du Canada, selon leur statut de minorité ou de majorité, présentent-elles le même profil santé ? Ont-elles accès aux mêmes services de santé et dans les mêmes conditions ? L’objectif de cet article cet article est de rendre compte des enjeux de santé reliés au fait d’appartenir à une minorité linguistique. Nos recherches permettent de mettre en évidence des disparités sociales et de santé qui peuvent être attribuées au fait minoritaire. Dans le contexte canadien des deux langues officielles, une politique de santé équitable devra dorénavant pren dre en considération la situation linguistique minoritaire comme déterminant de la santé. Abstract Official language minorities (Francophones outside of Quebec and Anglophones in Quebec) make up about 6.4% of the Canadian population. Even though the Canadian constitution gives legal equality status to French and English, there is still room to ask if this equality is maintained in the health sector. In other words, do Francophone and Anglophone communities of Canada have the same health profiles regardless of their minority or majority status? Do they have access to the same health services and in the same conditions? The objective of this paper is to identify the health issues associated with belonging to a linguistic minority. Our research allows us to highlight the social and health disparities that can be attributed to belonging to a minority. In the Canadian context, which has two official languages, an equitable health policy will have to take into consideration language as a determinant of health.

Minorités de langue officielle du Canada : égales devant la santé ? - Bouchard, Louise; Desmeules, Martin (Presses de l’Université du Québec, 2011)

Public policy and citizen-based practices that support social and health services for official and co-official language minority communities. An international perspective: What has really been achieved and what are the gaps | Politiques publiques et pratiques citoyennes soutenant les services sociaux et de santé pour les communautés minoritaires de langue officielle et coofficielles. Une perspective internationale : ce qui a été accompli et ce qui reste à faire - Bouchard, Louise; Nyqvist, Fredrica; Mari Mayans, Isidor; van Kemenade, Solange; Maisonneuve, Alexander. R. (Linguistic Minorities and Society / Minorités linguistiques et société, 2021)

Health profile of English-speaking minority communities in Quebec [infographic] - Bouchard, Louise; Sampasa-Kanyinga, Hugues; Mukaneza, Anne (2018)

Profil santé des communautés anglophones en situation minoritaire au Québec [infographie] - Bouchard, Louise; Sampasa-Kanyinga, hugues; Mukaneza, anne (2018)

Bilingual health care in Quebec: Public policy, vitality, and acculturation issues - Bourhis, Richard Y. (Accessibility and active offer: Health care and social services in linguistic minority communities, 2017)
Abstract The first part of this chapter offers the Interactive Acculturation Model (IAM), which provides an intergroup approach to minority/majority group relations in multilingual settings. The ethnolinguistic vitality framework is the first element of the IAM as it describes the relative strength and weaknesses of linguistic communities in contact. Four language policies regulating the status of linguistic communities constitute the key second element of the IAM. Third, the acculturation orientations of minority and majority group speakers are described as they interact to yield harmonious, problematic or conflictual intergroup relations. As an application of the IAM, the second part of the chapter analyzes bilingual health care policies for official language minorities in Canada and Quebec. A detailed analysis of bilingual health care institutions serving the English-speaking communities of Quebec closes with a case study of a recent Quebec Government health care law that threatened to undermine the institutional vitality of the Anglophone minority of Quebec. Key words: Interactive Acculturation Model (IAM), English-speaking communities of Quebec, health care policies.

The vitality of the English-speaking communities of Quebec: From community decline to revival - Bourhis, Richard Y. (Centre d’études ethniques des universités montréalaises, Université de Montréal, 2008)

Acculturation, vitality, and bilingual healthcare - Bourhis, Richard Y.; Montreuil, Annie (The Oxford handbook of acculturation and health, 2017)

Barrières linguistiques dans l'accès aux soins de santé - Bowen, Sarah (Santé Canada, 2001)

Language barriers in access to health care - Bowen, Sarah (Health Canada, 2001)

Comparaisons internationales : un aperçu de l'accès aux soins de santé pour les communautés de langue officielle en situation minoritaire au Canada, en Espagne, en Belgique et en Finlande - Bureau d'appui aux communautés de langue officielle (Santé Canada, 2007)

Programme de contribution pour l'amélioration de l'accès aux services de santé pour les communautés de langue officielle en situation minoritaire. Évaluation formative. - Bureau d'appui aux communautés de langue officielle (Santé Canada, 2007)

Quel avenir pour les services sociaux et de santé des communautés anglophones du Québec ? - Carter, Jane (Déclin et enjeux des communautés de langue anglaise du Québec, 2012)

Availability, accessibility and acceptability of english-language mental health services for the Estrie region’s english-speaking population: Service user and provider perspectives - Charpentier, Claude; Stout, Dale; Benoit, Annie; Poulin, Edith; Philip, Christopher (Journal of Eastern Townships Studies, 2011)
Mental illness affects about 1 in 5 Canadians during their lifetime but only approximately 30% of people needing help actually access mental health ser vices (Gravel, Connolly & Bédard, 2004). This low access rate is worrisome and may not accurately depict the reality as it is lived out by linguistic minorities. The present study documents both the need for and access to English-lan guage mental health services by the Estrie region’s English-speaking minority. Intending to record their needs and access experiences against the backdrop of available English-language mental health services, both users and providers of these services were surveyed in tandem. This novel approach to mental health needs assessment research shows the precarious situation of this minority community (high need/low access to language-congruent mental health ser vices) to be further compromised by misperceptions of service availability.

Talk COVID to me: Language rights and canadian government responses to the pandemic - Chouinard, Stéphanie; Normand, Martin (Canadian Journal of Political Science, 2020)
Since the COVID-19 outbreak, a gradual loosening of linguistic obligations in public institutions and governments has been observed in various jurisdictions in Canada. This article argues that in addition to legal requirements to provide minority language services, it is not justifiable for governments to suspend or curtail such services in an emergency situation, for reasons pertaining to public safety and public health. After performing a survey and analysis of government actions against their constitutional, legislative, and policy language obligations to highlight best practices and deficiencies, we discuss the policy implications of these actions. In conclusion, the article considers how governments could better uphold their language obligations in times of emergency.

L’offre active une culture de respect, une culture d’excellence : dépliant [infographie] - Commissariat aux langues officielles (2019)

L’offre active une culture de respect, une culture d’excellence : guide complet [infographie] - Commissariat aux langues officielles (2017)

Portrait des minorités de langue officielle au Canada : les anglophones du Québec - Corbeil, Jean-Pierre; Chavez, Brigitte; Pereira, Daniel (Statistique Canada, 2010)

Portrait of Official-Language Minorities in Canada: Anglophones in Quebec - Corbeil, Jean-Pierre; Chavez, Brigitte; Pereira, Daniel (Statistics Canada, 2010)

Les minorités prennent la parole : résultats de l'Enquête sur la vitalité des minorités de langue officielle - Corbeil, Jean-Pierre; Grenier, Claude; Lafrenière, Sylvie (Statistique Canada, 2007)

Minorities speak up: Results of the survey on the vitality ot the Official-Language Minorities - Corbeil, Jean-Pierre; Grenier, Claude; Lafrenière, Sylvie (Statistics Canada, 2007)

English-language Health and Social Services Access in Québec. Comparison 2019-2023 - CROP (Community Health & Social Services Network, 2023)

L’accès en anglais aux services de santé et aux services sociaux au Québec. Version française du rapport comparatif 2023-2019 - CROP (Community Health & Social Services Network, 2024)

L'accessibilité des services sociaux et de santé chez les minorités de langue officielle du Canada et les facteurs influant sur leur accès : une étude de portée - Éthier, Alexandra; Carrier, Annie (Minorités linguistiques et société, 2022)
Les minorités de langue officielle (MLO) du Canada rencontrent des difficultés d’accès aux services sociaux et de santé (SSS). Or, il n’existe aucun portrait exhaustif des services concernés par ces difficultés et des facteurs (facilitateurs et barrières) qui modulent leur accès. Ainsi, le but de cette étude était de décrire l’accessibilité des SSS et d’identifier les facteurs influant sur l’accès aux SSS pour les MLO canadiennes. Une étude de portée dans neuf banques de données combinée à une stratégie élargie a permis d’inclure 74 documents. Les SSS sont généralement insuffisants pour les MLO. De plus, 15 facteurs (8 facilitateurs, 11 barrières) ont été identifiés. Enfin, 26 connexions (une parmi les facilitateurs, 25 parmi les barrières) ont été notées, complexifiant l’accès aux SSS pour les MLO. Intervenir pour favoriser l’accès aux SSS des MLO pourrait être bénéfique à l’ensemble des populations canadiennes, étant donné la présence de barrières communes entre ces groupes. Mots-clés : services sociaux et de santé, minorité anglophone, minorité francophone, facilitateurs, barrières

Les disparités d'accès aux soins de santé parmi la minorité de langue officielle au Québec - Falconer, James; Quesnel-Vallée, Amélie (Recherches sociographiques, 2014)
Cette étude examine l’effet de l’aptitude en français sur la santé et sur les besoins de soins de santé non satisfaits au Québec, en utilisant un modèle multiple de régression logistique. Nos résultats indiquent que les anglophones unilingues du Québec sont 26 % plus susceptibles que les anglophones bilingues à se déclarer en mauvaise santé. Théoriquement, ce mauvais état de santé devrait mener à une utilisation accrue des soins de santé. Cependant, malgré leur mauvais état de santé, les anglophones unilingues sont 52 % plus susceptibles de déclarer des besoins en soins de santé non satisfaits. Ces disparités dans l’état de santé ainsi que dans l’accès aux soins de santé s’expliquent par l’aptitude à s’exprimer en français. Par ailleurs, ces effets ne sont pas modifiés par l’inclusion de variables potentiellement confondantes telles que les caractéristiques sociodémographiques et socioéconomiques. Les résultats suggèrent que ce sont les politiques visant à réduire les obstacles à l’accès aux soins de santé des populations minoritaires qui pourraient améliorer l’accès aux soins, et, éventuellement, la santé des anglophones unilingues du Québec. Mots-clés : populations minoritaires de langue officielle, anglophones, Québec, utilisation des services de santé, inégalités de santé, accès aux soins de santé

Seeking social services on the Gaspé coast: A narrative analysis of Anglophones’ experiences of access and care [master's thesis, University of Victoria] - Finlayson, S. (University of Victoria, 2017)
This research addresses the concern that Anglophone populations in the predominantly French speaking Gaspé region of eastern Québec are experiencing high rates of social problems such as poverty and unemployment. Anglophones in this region, as in other rural regions of Québec, have identified facing difficulties related to access to social services, an aspect which further complicates existing social problems. Using a narrative methodology and post structural, feminist and intersectional lenses, this research explores the experiences of English speaking service users in accessing and engaging with social services on the Gaspé coast. This study also explores the boundaries and reproduction of linguistic categories and identity and offers insight into resisting dominant discourses pertaining to linguistic difference in Québec, specifically within the context of social services. The results of this research demonstrate that service users’ experiences were characterised by disproportionately negative effects in regards to service access and delivery such as intensified logistical problems and social work practice related weaknesses. The research also concludes that experiences involved multiple, intersecting problems, which were irreducible to the singular dimension of language. The intersections of language and race, language and class, and language and ability were raised as critical concerns in terms of access to social services on the Gaspé coast. Finally, the encounters between Anglophones and Francophones in the context of health and social services in the region were found to be entangled and inseparable from the historical and ongoing political struggles over language on this territory.

Access to health care services and self-perceived health of canada's official-language minorities [master's thesis, University of Ottawa] - Gagnon-Arpin, Isabelle (University of Ottawa, 2011)

Accès et utilisation des services de santé en langue minoritaire - Gagnon-Arpin, Isabelle; Bouchard, Louise; Leis, Anne; Bélanger, Mathieu (La vie dans une langue officielle minoritaire au Canada, 2014)

Access and use of health care services in the minority language - Gagnon-Arpin, Isabelle; Bouchard, Louise; Leis, Anne; Bélanger, Mathieu (Life within an official language minority in Canada, 2014)

Portrait des services bilingues offerts au sein des hôpitaux canadiens. Rapport - Guignard Noël, Josée; LeBlanc, J.; Forgues, Éric (Institut canadien de recherche sur les minorités linguistiques, 2016)

Étude de référence sur les services bilingues au sein des établissements de santé canadiens - Guignard Noël, Josée; LeBlanc, Joannie; Forgues, Éric (Institut canadien de recherche sur les minorités linguistiques, 2016)

Frontières linguistiques et culturelles : le cas de l’accessibilité aux services de santé et de services sociaux pour la population anglophone de la région de Québec - Hanrahan, Louis; Cloutier, Annabelle; Walling, Richard (Cahiers de l’ÉDIQ, 2016)

Access to Health and Social Services in Official Languages (Reaffirmation) - Health Standards Organization (2022)
The standard CAN/HSO 11012:2018 (R2022) is a reaffirmation of CAN/HSO 11012:2018 Access to Health and Social Services in Official Languages. The standard provides guidelines of excellence to help organizations aim to improve access to health and social services across the continuum of care in Canada’s two official languages – French and English. The standard content is grouped into five sections: - Establishing the Active Offer of Services - Clinical Research - Governance and Leadership - Workforce - Quality Assurance

Client and family information sheet: Access to health and social services in Official Languages Standard - Health Standards Organization (2018)
The CAN/HSO 11012:2018 Access to Health and Social Services in Official Languages Standard provides guidelines of excellence to help organizations aim to improve access to health and social services across the continuum of care in Canada’s two official languages – French and English. This information sheet explains what should be expected from health and social service organizations applying this standard.

Accès aux services de santé et aux services sociaux dans les langues officielles - Health Standards Organization / Organisation de normes en santé (2018)
La norme CAN/HSO 11012:2018 intitulée Accès aux services de santé et aux services sociaux dans les langues officielles fournit des lignes directrices d’excellence pour aider les organismes à améliorer l’accès aux services de santé et aux services sociaux à l’intérieur du continuum de soins dans les deux langues officielles du Canada, soit le français et l’anglais.

Accès aux services de santé et aux services sociaux dans les langues officielles (confirmation) - Health Standards Organization / Organisation de normes en santé (2022)
La norme CAN/HSO 11012:2018 (R2022) est une confirmation de la norme CAN/HSO 11012:2018 intitulée Accès aux services de santé et aux services sociaux dans les langues officielles. Elle fournit des lignes directrices d’excellence pour aider les organismes à améliorer l’accès aux services de santé et aux services sociaux à l’intérieur du continuum de soins dans les deux langues officielles du Canada, soit le français et l’anglais. Le contenu de la norme comprend cinq sections : - Établissement de l’offre active de services - Recherche clinique - Gouvernance et leadership - Main-d’oeuvre - Assurance de la qualité

Feuillet d'information pour les usagers et les familles : norme sur l'Accès aux services de santé et aux services sociaux dans les langues officielles - Health Standards Organization / Organisation de normes en santé (2018)
La norme CAN/HSO 11012:2018 intitulée Accès aux services de santé et aux services sociaux dans les langues officielles fournit des lignes directrices d’excellence pour aider les organismes à améliorer l’accès aux services de santé et aux services sociaux à l’intérieur du continuum de soins dans les deux langues officielles du Canada, soit le français et l’anglais. Ce feuillet d'information explique ce à quoi les usagers peuvent s'attendre des organismes de santé et de services sociaux qui appliquent cette norme.

Comprendre l’expérience des soins de longue durée des minorités de langue officielle au Canada : état des lieux - Hsu, Amy. T.; Ménard, Alixe; Scott, Mary (Université d'Ottawa et Institut de recherche Bruyère, 2022)

Understanding the long-term care experience of official language minorities in Canada: An environmental scan - Hsu, Amy; Ménard, Alixe; Scott, Mary (Bruyère Research Institut, 2022)

Identifying second language speech tasks and ability levels for successful nurse oral interaction with patients in a linguistic minority setting: An instrument development project - Isaacs, Talia; Laurier, Michel. D.; Turner, Carolyn. E.; Segalowitz, Norman (Health communication, 2011)
One of the most demanding situations for members of linguistic minorities is a conversation between a health professional and a patient, a situation that frequently arises for linguistic minority groups in North America, Europe, and elsewhere. The present study reports on the construction of an oral interaction scale for nurses serving linguistic minorities in their second language (L2). A mixed methods approach was used to identify and validate a set of speech activities relating to nurse interactions with patients and to derive the L2 ability required to carry out those tasks. The research included an extensive literature review, the development of an initial list of speech tasks, and validation of this list with a nurse focus group. The retained speech tasks were then developed into a questionnaire and administered to 133 Quebec nurses who assessed each speech task for difficulty in an L2 context. Results were submitted to Rasch analysis and calibrated with reference to the Canadian Language Benchmarks, and the constructs underlying the speech tasks were identified through exploratory and confirmatory factor analyses. Results showed that speech tasks dealing with emotional aspects of caregiving and conveying health-specific information were reported as being the most demanding in terms of L2 ability, and the most strongly associated with L2 ability required for nurse–patient interactions. Implications are discussed with respect to the development and use of assessment instruments to facilitate L2 workplace training for health care professionals.

Do you speak English? Traitement sociopolitique de l’accessibilité aux services en santé mentale pour les anglophones du Québec - Kirouac, Laurie; Perreault, Isabelle (Minorités linguistiques et société, 2018)
À la fin des années 1970, le Québec se dote de la Charte de la langue française (Loi 101), qui modifie l’encadrement de la question de la langue de prestation des services de santé et de services sociaux. Parallèlement, de nombreux rapports, comités d’étude et politiques modifient en profondeur les pratiques institutionnelles et communautaires à l’endroit des personnes aux prises avec des problèmes de santé mentale. Depuis ce contexte de grandes transformations, où certaines réponses politiques ont été apportées aux préoccupations linguistiques, qu’en est-il de l’accès aux soins de santé mentale pour les anglophones du Québec ? Nous proposons de retracer dans ses grandes lignes l’évolution du traitement sociopolitique qui a été fait de la question de l’accessibilité des services en santé mentale pour les personnes anglophones en accordant une attention particulière à la situation montréalaise. Mots-clés : Québec, anglophones, santé mentale, minorité linguistique, services de santé

Les services de santé au Canada : une perspective linguistique - Lacroix, Frédéric (L'Action nationale, 2006)

La parole aux communautés : nous sommes là! La vitalité des communautés de langues officielles en situation minoritaire. Rapport du Comité permanent des langues officielles - Lauzon, Guy (Gouvernement du Canada, Chambre des communes 39e Législature, 1er session, 2007)

La bilinguisation des services de santé et des services sociaux du Québec - Lefebvre, Mathilde (Institut de recherche en économie contemporaine, 2014)

Perceptions des communautés de langue officielle en situation minoritaire : accès aux services de santé dans la langue officielle de son choix. Rapport final - Léger (Santé Canada, 2020)

Comprendre l'expérience des soins de longue durée des minorités de langue officielle au Canada : une analyse de l'environnement | Understanding the long-term care experience of official language minorities in Canada: An environmental scan - Ménard, Alixe; Scott, Mary; Hsu, Amy T. (2022)

Guide pour l’élaboration du programme d’accès aux services de santé et aux services sociaux en langue anglaise - Ministère de la santé et des services sociaux (2018)

L'accès aux soins de santé des communautés de langue officielle en situation minoritaire (CLOSM) au Canada : une recension des écrits - Muray, Mwali; Peguero-Rodriguez, G.; Scarlett, Emilie; Perron, Amélie; Chartrand, Julie (Minorités linguistiques et société, 2022)
Cette étude présente une recension des écrits sur les expériences des patients et des prestataires de soins en ce qui concerne les services de santé au Canada offerts aux communautés de langue officielle en situation minoritaire (CLOSM). Mandatée par le Bureau d’appui aux communautés de langue officielle (BACLO), cette recension fait constat des défis et des obstacles qui entravent l’offre de services de santé et l’accès aux soins pour les CLOSM dans la langue officielle de leur choix, et propose des recommandations à l’intention des patients, des professionnels de la santé, des établissements de santé, des différents ordres de gouvernement au Canada et des chercheurs. Cette recension des écrits met en lumière le manque d’exécution systémique des stratégies, afin de faciliter l’accès aux services de santé dans leur langue pour les CLOSM fondées sur des données probantes. Elle s’interroge également sur le fait que peu de stratégies fondées sur des données probantes ont été mises en oeuvre à l’échelle du système malgré des décennies de recherche sur le sujet. Mots-clés : accès aux soins de santé, communautés de langue officielle en situation minoritaire (CLOSM), patients, professionnels de la santé, recension des écrits

Language barriers: Use of regular medical doctors by Canada's official language minorities - Ngwakongnwi, Emmanuel; Hemmelgarn, Brenda, R.; Musto, Richard; King-Shier, Kathryn M.; Quan, Hude (Canadian Family Physician, 2012)

« Bâtir sur les fondations - améliorer les résultats pour la santé et accroître la vitalité des communautés anglophones du Québec ». Rapport présenté au ministre fédéral de la santé - Nouvet, Marcel; Maldoff, Eric (Comité consultatif des communautés anglophones en situation minoritaire, 2007)

“Building on the foundations, working toward better health outcomes and improved vitality of Quebec's English-speaking communities”. Report to the Federal Minister of Health - Nouvet, Marcel; Maldoff, Eric (Consultative Commitee for English-Speaking Minority Communities, 2007)

Contribution Program to improve access to health services for Official Language Minority Communities. Formative evaluation. - Official Language Community Development Bureau (Health Canada, 2007)

Adaptation linguistique des soins et des services de santé : enjeux et stratégies - Ouimet, Anne-Marie; Trempe, Normand; Vissandjée, Bilkis; Hemlin, Isabelle (Institut national de santé publique du Québec, 2013)

Language adaptation in health care and health services: Issues and strategies - Ouimet, Anne-Marie; Trempe, Normand; Vissandjée, Bilkis; Hemlin, Isabelle (Institut national de santé publique du Québec, 2013)

Accès aux services de santé et aux services sociaux en anglais au Québec. Rapport de données de base 2005-2006 - Pocock, Joanne (Réseau communautaire de santé et de services sociaux, 2006)

English-language health and social services access in Québec. Baseline data report 2015-2016 - Pocock, Joanne (Community Health and Social Services Network, 2016)

Quebec’s English-speaking community and the partnership approach of its networks in health - Pocock, Joanne (Linguistic Minorities and Society, 2021)
This article discusses the networking and partnership approach of improving access to public health and social services, with an interest in informing best practices for official language populations in a minority context. The case of Canada’s official language minority residing in the province of Quebec and its Community Health and Social Services Network (CHSSN) is explored. Elements that support or inhibit partnership functioning, including innovative community-based participatory evaluation (CBPE) techniques, are explored. The contribution of the approach in improving the situation of Quebec’s minority language communities with respect to their health care access is highlighted. Keywords: official language minority communities, intersectoral partnerships, access to public health care, language policy, community-based participatory evaluation (CBPE)

Accès interrégional aux services sociaux et de santé pour les personnes d’expression anglaise de l’est de Québec - Richardson, Mary; Gagnon, Hélène (Committee for Anglophone Social Action et Partenaires communautaires Jeffery Hale, 2015)
Cette étude visait à mieux comprendre ce que vivent les anglophones des régions de l‘est du Québec qui doivent se déplacer vers des centres urbains pour recevoir des services de santé spécialisés.

The network’s approaches for the maintenance and creation of primary health services in English for the Quebec City region - Sanderson, Duncan; Grégoire, Louise; Reinharz, Daniel (Agence de la santé et des services sociaux de la Capitale-Nationale & Direction régionale de santé publique, 2006)

Pratique # 15 : Le volet « santé et services sociaux » de l’Association des Townshippers (Québec) - Savard, Jacinthe; Savard, Sébastien; van Kemenade, Solange; Benoît, Josée; Buhay, Corrina; Youbi, Sara; Kubina, Lucy-Ann (2019)

Directory of innovative practices in health and social services in official language minority contexts - Savard, Jacinthe; Savard, Sébastien; van Kemenade, Solange; Benoît, Josée; Buhay, Corrina; Youbi, Sara; Kubina, Lucy-Ann; Dagnogo, Djenaba Sarah; Michel, Jean Nephetaly

Répertoire de pratiques novatrices en santé et service social en langue officielle en contexte minoritaire - Savard, Jacinthe; Savard, Sébastien; van Kemenade, Solange; Benoît, Josée; Buhay, Corrina; Youbi, Sara; Kubina, Lucy-Ann; Dagnogo, Djenaba Sarah; Michel, Jean Nephetaly

Exploring the determinants of language barriers in health care (LBHC): Toward a research agenda for the language sciences - Segalowitz, Norman; Kehayia, Eva (The Canadian Modern Language Review, 2011)
There is growing interest in language barriers in health care (LBHC) – interest, that is, in how the quality of health care service delivery might be compromised when patients and health care providers do not share the same first language. This article discusses LBHC as an emerging research area that provides valuable opportunities for researchers in various branches of the language sciences – including, among others, applied linguistics, theoretical linguistics, psycholinguistics, second language acquisition – to conduct basic research and to make contributions to the socially important area of medical communication. This article also proposes a research agenda aimed at attracting general language researchers to the study of LBHC, an agenda that is theory driven, programmatic, problem-solving oriented, and interdisciplinary in scope. In proposing this agenda, selected examples have been reviewed from the current literature that can serve as illustrative models for how future research into LBHC can proceed.

Access to health and social services for Quebec’s English-Speaking Minority Communities: Recent challenges, legislative context, and research recommendations. - Shoumarova, Lina (Quebec English-Speaking Communities Research Network, 2024)

Pour des services de santé culturellement et linguistiquement adaptés - Tremblay, Suzanne (Société Santé en français et Société Santé et Mieux-être en français du Nouveau-Brunswick, 2011)
Ce document fait rapport des études : Les normes de compétences culturelles et linguistiques en santé : étude exploratoire sur les normes américaines et Étude sur les services de santé linguistiquement et culturellement adaptés : portrait pancanadien.

Enjeux des services sociaux et de santé en contexte bilingue ou multilingue national. Revue de littérature - van Kemenade, Solange; Forest, Mariève (Secrétariat national du Consortium national de formation en santé, 2015)

Vers une démarche concertée pour le renforcement de la recherche sur les langues officielles dans le secteur de la santé : bilan et pistes d’action - Vézina, Sylvain; Doiron Robichaud, Johannie (Bureau d’appui aux communautés de langue officielle de Santé Canada, 2011)

Active offer, actors, and the health and social service system: An analytical framework - Vézina, Sylvain; Savard, Sébastien (Accessibility and active offer: Health care and social services in linguistic minority communities, 2017)

Offre active, acteurs et système de santé et de services sociaux : un cadre d’analyse - Vézina, Sylvain; Savard, Sébastien (Accessibilité et offre active : Santé et services sociaux en contexte linguistique minoritaire, 2017)
Résumé Ce chapitre présente un cadre théorique inspiré de l’analyse stratégique aussi nommée sociologie des organisations. Par cette approche, le chercheur tente de découvrir les objectifs et stratégies des acteurs en présence pour mieux saisir la dynamique du système d’action tout en prenant en compte les contraintes issues de la structure formelle. On y traite des concepts de système d’action, de pouvoir, de règle du jeu, de changement, de stratégie, d’acteur, d’enjeu, d’organisation et d’environnement, lesquels rendent compte de la complexité des défis entourant la pratique de l’offre active en santé et services sociaux. Une des contributions majeures de cette approche est qu’elle fournit un cadre d’analyse permettant de mieux saisir la relation entre l’acteur et le système, deux composantes essentielles tant à la compréhension de notre objet qu’à l’identification de stratégies d’action par les acteurs du milieu. Mots-clés : offre active, services sociaux et de santé, système d’action, pouvoir, zone d’incertitude, analyse stratégique, sociologie des organisations, changement, stratégie, acteur, enjeu, organisation, environnement.

Validation de l'équité d'accès des CLOSM aux professionnels de la santé dans les régions sociosanitaires du Canada - Warnke, Jan; Bouchard, Louise (Revue canadienne de santé publique / Canadian Journal of Public Health, 2013)
Objectifs Notre recherche utilise l’indicateur synthétique régional (IPSLOM) pour mesurer la capacité du système de santé à fournir un accès équitable aux professionnels de la santé pour les deux millions de personnes qui constituent des Communautés de langue officielle en situation minoritaire (CLOSM) dans 104 régions sociosanitaires du Canada. Méthode L’indicateur synthétique l’IPSLOM compare l’accès potentiel aux professionnels de la santé de la population de langue officielle minoritaire à l’accès potentiel de la population de langue officielle majoritaire. L’IPSLOM utilise 22 professions de santé, soit 79 % des effectifs de santé au Canada (Statistique Canada, 2006) qui ont à communiquer avec leur clientèle dans un but thérapeutique ou diagnostique. Résultats L’indice comparatif de l’IPSLOM a révélé que la population CLOSM de 10 des 13 provinces/territoires du Canada est désavantagée par rapport à la majorité linguistique quant à l’accès potentiel aux professionnels de la santé capable de les desservir en langue minoritaire. La population CLOSM est désavantagée en Ontario dans 13 régions sociosanitaires sur 14, au Québec dans 17 régions sur 18 et au Nouveau-Brunswick dans 3 des 7 régions sociosanitaires. Conclusion L’indicateur synthétique IPSLOM a permis d’identifier des inégalités d’accès aux professionnels de la santé entre la minorité de langue officielle et la majorité linguistique, à travers les régions sociosanitaires du système de santé au Canada. Des analyses plus fines de l’IPSLOM par professions spécifiques permettraient d’approfondir notre connaissance des inégalités de santé qui affectent les communautés de langue officielle en situation minoritaire.